Travels with Charley and later novels, 1947-1962 - Steinbeck, John, 1902-1968 (Library of America, 2007)
A final installment of a four-part collection of the classic American writer's works features his later novels, including "The Wayward Bus," "Burning Bright," "Sweet Thursday," and "The Winter of Our Discontent," in a volume that is complemented by his final published account, "Travels with Charley."